Surveillance and Control of Threats in the Public Health System in Brazil: Mapping Managers' Competencies. Issue Volume 34:Issue s1(2019) (May 2019) - Silva, Marcio Haubert Da; Albini, Alessandro; Witt, Regina Rigatto
Abstract : Introduction: With the increase in the number and intensity of disasters, integrated risk management has been a subject of discussion in Brazilian health system, in which the local level plays an important role. Competency Mapping of Managers working at a Municipal Health Office from a Metropolitan Area of Curitiba, Southern Brazil was developed. Aim: To describe gaps in core competencies identified for Surveillance and Control of Risks and Threats. Methods: The Public Health Core Competencies contained in the booklet: A Regional Framework for the Americas, of the Pan American Health Organization, originated a semi-structured self-assessment questionnaire. A Likert scale with levels of proficiency (from one to five) was aggregated to the 56 specific core competencies. It was applied to a sample of 78 managers between the months of October 2017 and January 2018. The data obtained were submitted to quantitative analysis. Gaps (Training Priority Degree) were defined according to the grade of importance and expression by means of a arithmetic mean and standard deviation. Results: Gaps were identified for the competencies: Design disaster risk management plans for natural, technological and biological threats so as to mitigate their impact on health (2.82 ± 1.16); Design investment projects for reducing the health risks of disasters (2.8 ±1.07); Provide an immediate response to threats, risks and damage from disasters based on the risk assessment, in order to protect health (2.89 ± 1.13); Plan and execute post-disaster reconstruction, based on the damage identified for the immediate restoration and protection of the population's health (2.81 ± 1.11). Discussion: The degree of expression for these competencies indicate the need of preparing public health managers for surveillance, by monitoring the exposure of people or population groups to environmental agents, or their effects with an integrated approach to injuries and the etiology of emergencies and disasters.